2019
DOI: 10.1016/j.jconrel.2019.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic toxicity of silica nanoparticles as a function of size and porosity

Abstract: Despite increasing reports of using silica nanoparticles (SNPs) for controlled drug delivery applications, their long-term toxicity profile following intravenous administration remains unexplored. Herein, we investigated the acute (10-day) and subchronic (60-day and 180-day) toxicity of nonporous SNPs of approximately 50 nm (Stöber SNPs50) and approximately 500 nm in diameter (Stöber SNPs500), and mesoporous SNPs of approximately 500 nm in diameter (MSNPs500) upon single-dose intravenous injection into male an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 43 publications
1
63
0
Order By: Relevance
“…Tunable properties of NPs, such as shape, surface charge, and size, may affect their toxicity (135,136). For instance, cerium oxide (CeO 2 ) NPs with rod-like shape showed higher and dosedependently enhanced macrophage cytotoxicity responses with respect to cubic/octahedral NPs (137).…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
“…Tunable properties of NPs, such as shape, surface charge, and size, may affect their toxicity (135,136). For instance, cerium oxide (CeO 2 ) NPs with rod-like shape showed higher and dosedependently enhanced macrophage cytotoxicity responses with respect to cubic/octahedral NPs (137).…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%
“…The Liver is the main organ for spherical Stöber and mesoporous silica nanoparticles accumulation 10 days and 60 days following single dose intravenous administration at MTD which can be cleared at the 180 th day. [165] Our results show that at 180 days post single dose intravenous administration of the nanoparticles, subchronic tissue toxicity of SNPs is influenced by the size of the particles. Liver and spleen recovery in mice following administration of the larger Stöber SNPs (432 ± 18.7 nm in diameter with −53.1 ± 1.5 mV zeta potential) took a longer period (180 days) compared to administration of the smaller Stöber SNPs (46 ± 4.9 nm; −40.3 ± 1.9 mV).…”
Section: Specific Tissue Toxicitymentioning
confidence: 67%
“…[146] The size of Stöber silica nanoparticles influences the recovery time needed for Balb/c mice from blood and tissue toxicity and inflammation induced symptoms by 50 and 500nm SNPs at MTD dose. [165] Therefore, it seems that long-term toxicity of inorganic nanoparticles, as well as their acute toxicity, are significantly affected by their size. Since the source of nanoparticles and the animal strain as well as experimental conditions are different in these studies, it cannot be concluded if there is a linear correlation or any specific size range that shows higher or lower toxicity.…”
Section: Physiochemical Properties-mentioning
confidence: 99%
See 2 more Smart Citations